Pemanfaatan Bibit Unggul dan Pupuk Semi Organik untuk Ketahanan Pangan Berbasis Sistem Dinamis - Sugianto, Arla Meica Regita; Murnawan, Hery (SURYA TEKNIKA, 2025)
Sumber kepuh Village in Tanjunganom Sub-district, Nganjuk District, covers 763 hectares with 78% of it being paddy fields, making it the largest rice producer in the sub-district. However, farmers are still struggling to increase harvest profits. Analysis using SmartPLS showed that the dominance of elderly farmers as well as environmental factors such as fertilizer type, soil pH, and seed quality had a significant effect on yield. A dynamic systems approach through STELLA resulted in three profit improvement scenarios. The first scenario uses superior seeds and a young planting system, increasing profits from IDR 27,487,047,641 to IDR 31,983,065,202 (up 16%). The second scenario, using semi-organic fertilizers, increased profits to IDR 39,072,970,965 (up 42%). The third scenario, a combination of both, yielded IDR 40,568,583,572 (a 48% increase). The third scenario is considered the most optimal in improving farmers' welfare and encouraging the regeneration of young farmers to maintain long-term food security in Sumberkepuh Village.